2001
DOI: 10.1161/01.cir.103.8.1148
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Resetting Reentrant Circuits in Canine Ventricular Tachycardia

Abstract: Multiple mechanisms revealed by mapping cause resetting of reentrant circuits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…It is likely that this observation results from a combination of properties of the DP, including structural features, such as change in muscle fiber orientation causing conduction anisotropy at entry to and within the DP (demonstrated in the canine infarct model) (1,3,12), and functional factors, including current source/sink relationships and altered gap-junctional organization (16). We have previously demonstrated that the greatest degree of conduction slowing in human infarct-related VT circuits occurs at changes of trajectory within the DP (10).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is likely that this observation results from a combination of properties of the DP, including structural features, such as change in muscle fiber orientation causing conduction anisotropy at entry to and within the DP (demonstrated in the canine infarct model) (1,3,12), and functional factors, including current source/sink relationships and altered gap-junctional organization (16). We have previously demonstrated that the greatest degree of conduction slowing in human infarct-related VT circuits occurs at changes of trajectory within the DP (10).…”
Section: Discussionmentioning
confidence: 99%
“…We have previously examined the interaction between extrastimuli and functional components of VT circuits and properties of the EGap in the well characterized canine infarct model with epicardial isochronal mapping (3,12). We demonstrated that temporal and spatial qualities of the EGap vary at different points within the circuit (12).…”
mentioning
confidence: 99%
“…Many studies were carried out to specify the nature and the importance of excitable gaps during reentry in the anisotropic myocardium (7,116,125,248,253,295,360). It should be pointed out that there are no major differences in the principles that govern the behavior of rotors and spiral waves in isotropic and anisotropic media as long as the media are continuous, i.e., devoid of discontinuities in passive or active electric properties (167,248,373).…”
Section: Relation Between Excitable Gaps and Structurementioning
confidence: 99%
“…Cardiac conduction velocity (CV) describes the speed and direction of propagation of the action potential wavefront through myocardium. It can provide important quantitative electrophysiological information about the underlying tissue microarchitecture and is widely used in both laboratory [1,2] and clinical electrophysiological studies [3,4] to infer properties of the myocardial substrate and to identify potential mechanisms for arrhythmogenesis [5–7] . Conduction velocity measurements provide an important quantity in identifying potential reentrant circuits and regions of tissue which, for example, might act as an anchor point for rotors [8] .…”
Section: Introductionmentioning
confidence: 99%